Financial Sector Assessment Program : Malawi - Access to Financial Services - International Monetary Fund; World Bank (World Bank, Washington, DC, 2013)
This technical note the Malawi 2007 Financial Sector Assessment Program (FSAP) reviews the current challenges of increasing access to financial services in Malawi. After a cursory assessment of the state of the financial sector in chapter one, it summarizes the key challenges of rural financial sector development (chapter two); then discusses the opportunities that branchless banking technology offers (chapter three), the options for strengthening the financial infrastructure (chapter four) and the role of government in increasing access (chapter five). It concludes with recommendations on how authorities may seek to realize these opportunities (chapter six).